CHARACTERIZATION OF MODIFIED BENTONITE USING ALUMINUM POLYCATION - Hery Haerudin; Nino Rinaldi; Adel Fisli (Universitas Gadjah Mada, 2002)
The modification of bentonite by pillarization using aluminum polycation type Keggin [Al13O4(OH)24(H2O)12]7+ has been carried out, by exchange of cation from interlayer with aluminum polycation. The amount of aluminum polycation, which was used for the pillaring of bentonite was varied, i.e. 5 mmol/gram, 10 mmol/gram, and 20 mmol/gram of bentonite. After drying, the pillared bentonite was calcined at 400 oC for 6 hour with temperature rate of 5 oC/min. The cationic exchange capacity (CEC) of starting bentonite was 98.3 meq/100 gram. The concentration ratio of Al/Si increased from 0.27 to 0.34 for pillared bentonite and of Ca/Si was decreased from 0.06 to 0.006 for pillared bentonite. The basal space for pillared bentonit increased significantly from 7.30 Å to about 18 Å . The measured specific surface area (by BET) of pillared bentonite was also increased significantly from 46 m2/g to about 162 m2/g. It was concluded that bentonite has been pillared by aluminum polication successfully.